Tinjauan Kriminologi Tindak Pidana Membawa Senjata Tajam - Jaya, Bagus Novian; Abadi, Suwarno (Gorontalo Law Review, 2025)
The crime of carrying sharp weapons in Indonesia is a serious issue that threatens public security and public order. This study aims to analyze the legal framework concerning the crime of carrying sharp weapons and to identify the countermeasures implemented by the government and law enforcement agencies. This research uses a normative juridical method with approaches including the Statute Approach, Case Approach, and analysis of societal habits related to carrying sharp weapons. The results show that although clear regulations exist, their effectiveness in preventing the misuse of sharp weapons, particularly in crowded situations, remains questionable. A stricter enforcement of the law is necessary to create a deterrent effect for offenders, while non-penal approaches, such as legal awareness campaigns, are also essential to educate the public about the dangers and socialization of carrying sharp weapons without permission. The synergy between the government, law enforcement, and society is crucial to creating order and security in public spaces, ensuring that existing regulations are applied optimally.